ANALYSIS OF THE EFFECTIVENESS OF ANDALIMAN FRUIT EXTRACT ZANTHOXYLUM PIPERITUM IN WOUND HEALING AFTER TOOTH EXTRACTION IN WISTAR RATS - Yang Yang (EPRA International Journal of Research and Development (IJRD), 2023)
Andaliman contains phenol compounds, monoterpenes, sesquiterpenes, nones, and essential oils, a class of terpenoid compounds. Based on its chemical content and physiological activity, andaliman can be used as a spice, preservative, medicinal material and supplement, and vegetable pesticide. The study aimed to analyze the effectiveness of andaliman (Zanthoxylum piperitum) fruit extract 40% and 80% in wound healing after tooth extraction in rats. This laboratory experimental study used a complete randomized design with a post-test-only control group design pattern. The experimental animals used in this study were 32 male Wistar rats, physically healthy, 2-3 months old, with body weight between 200-250 grams. The rats will be divided into two groups, namely 16 rats treated with 40% Andaliman fruit (Zanthoxylum piperitum) and 16 rats treated with 80% Andaliman fruit (Zanthoxylum piperitum) to see the comparison of accelerated wound healing after tooth extraction. The study used a pure experiment with a non-parametric Chi-Square Test after the test showed that (p<0.05) means a significant difference between groups. The results showed that there was a meaningful relationship between the number of fibroblast tissue per visual field in Wistar rats after tooth extraction by giving Andaliman Fruit Extract (Zanthoxylum piperitum) at 40% concentration and Andaliman Fruit Extract (Zanthoxylum piperitum) 80% concentration, p=0.010 (p<0.05). Based on the results and discussion that has been done in this study, it can be concluded that Andaliman Fruit Extract (Zanthoxylum piperitum) 40% and 80% effectively accelerate wound healing time after tooth extraction of Wistar rats